Evidence of biogeomorphic patterning in a low‐relief karst landscape. Issue 15 (10th June 2014) - Watts, Adam C.; Watts, Danielle L.; Cohen, Matthew J.; Heffernan, James B.; McLaughlin, Daniel L.; Martin, Jonathan B.; Kaplan, David A.; Osborne, Todd Z.; Kobziar, Leda N.
ABSTRACT Patterned landscapes are often evidence of biotic control on geomorphic processes, emerging in response to coupled ecosystem processes acting at different spatial scales. Self‐reinforcing processes at local scales expand patches, while self‐inhibiting processes, operating at a distance, impose limits to expansion. In Big Cypress National Preserve (BICY) in southwest Florida, isolated forested wetland depressions (cypress domes) appear to be evenly distributed within a mosaic of short‐hydroperiod marshes and pine uplands. To test the hypothesis that the apparent patterning is regular, we characterized frequency distributions and spatial patterns of vegetation communities, surface and bedrock elevation, and soil properties (thickness and phosphorus content). Nearest neighbor distances indicate strongly significant wetland spatial overdispersion, and bedrock elevations exhibited periodic spatial autocorrelation; both observations are consistent with regular patterning. Bedrock elevations and soil P were clearly bimodal, suggesting strong positive feedbacks on wetland patch development. Soil‐surface elevations exhibited weaker bimodality, indicating smoothing of surface morphology by some combination of sediment transport, mineral reprecipitation, and organic matter production. Significant negative autocorrelation of bedrock elevations at scales similar to wetland spacing suggest the presence of distal negative feedbacks on patch expansion. These findings support the inference of regular patterning, and are consistent with the presence of local positive feedbacks among hydroperiod, vegetation productivity and bedrock dissolution. These processes are ultimately constrained by distal negative feedbacks, potentially induced by landscape scale limitations on the water volume required to enable this biogeomorphic mechanism. Copyright © 2014 John Wiley & Sons, Ltd.